2020
DOI: 10.5435/jaaos-d-18-00728
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With In-Hospital Outcomes of Traumatic Spinal Cord Injury: 10-year Analysis of the US National Inpatient Sample

Abstract: Introduction: Traumatic spinal cord injury (SCI) is a life-altering event. Motor vehicle accidents and falls are common causes of traumatic SCI, and SCI outcomes may be affected by patients' ages and injury sites. This study aimed to investigate the factors associated with unfavorable in-hospital outcomes, focusing on the impact of patients' ages and SCI lesion sites. Methods: Data of 25,988 patients hospitalized with traumatic SCI in the US National In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…The result of our study still cannot infer a causal relationship between operative treatment and lower mortality, because it did not record the severity of the injury and other aspects of the patient’s condition (e.g. neurological involvement) that might influence the surgeon’s decision to perform surgery 13 , 17 , 30 , 55 , 56 . The utilization of operative treatment is also associated with several challenges (e.g.…”
Section: Discussionmentioning
confidence: 88%
“…The result of our study still cannot infer a causal relationship between operative treatment and lower mortality, because it did not record the severity of the injury and other aspects of the patient’s condition (e.g. neurological involvement) that might influence the surgeon’s decision to perform surgery 13 , 17 , 30 , 55 , 56 . The utilization of operative treatment is also associated with several challenges (e.g.…”
Section: Discussionmentioning
confidence: 88%
“…More than 30 candidate variables were used in CART analysis, and age (≤63 or >63 years) was identified as the factor most likely to influence the likelihood of independent living. Gao et al [18] have investigated the factors associated with unfavorable in-hospital outcomes, focusing on the impact of patients' age and lesion site using the US national inpatient sample. Their multivariate analysis revealed that older age (>65 years) was significantly associated both with increased in-hospital mortality and increased adverse outcomes, regardless of the lesion site.…”
Section: Discussionmentioning
confidence: 99%
“…Tout d'abord, ces résultats peuvent être expliqués par une incidence plus forte de certaines de ces pathologies aux âges plus jeunes [32][33][34][35]. Ensuite, les personnes ayant des pathologies psychiatriques ou certaines pathologies neurologiques ont des espérances de vie plus faibles qu'en population générale et des taux de mortalité plus importants [36][37][38][39][40][41].…”
Section: Discussionunclassified